The importance of climate scenarios in setting the productivity indexes in the Pampa Arenosa sub-region of the province of Buenos Aires, Argentina - Silvia Patricia Pérez (Revista Ambiente & Água, 2019)
Starting in the 1970's, the Pampa Arenosa sub-region experienced an increasing water regime that generated an increased area for dryland farming. With increasing agricultural activity, examining the land is an essential strategic tool for its planning. The objective of this work was to highlight the importance of considering several climate scenarios when setting the productivity index in the sector of longitudinal dunes in the Pampa Arenosa sub-region in the province of Buenos Aires, Argentina. The climate scenarios were set in relation to the shifts in average rain values, according to the Pettitt Test. The land were classified according to their productivity index. It was found that the productivity index of the land increased with the rain, reaching its highest value in the period right after the abrupt shift. Land of moderate productive capacity whose productivity index values are between 65 and 51 comprised the majority of the area of our study.